Analysis of support and identification of barriers to SMEs in Slovakia and in the Czech Republic - Labudová, Lenka; Jánošová, Denisa (Serbian Journal of Management, 2019)
The aim of the paper is to identify main obstacles in small and medium enterprises and evaluate similar and different features of the state support for entrepreneurship in Slovakia and the Czech Republic, based on detailed analysis and data from questionnaire research. Paper is divided into 5 chapters. In the introduction, authors are trying to focus on purpose of why it is important to support SMEs. The second chapter defines entrepreneurial support and individual support programs for SMEs in the Czech Republic and Slovakia by the European Union and by individual countries. The third chapter focuses on selected questions from research, which was made under the auspices of the project “How to prevent SMEs from failure”. It´s followed by a discussion and conclusion in which authors point out the biggest obstacles to SMEs that prevent them from successfully remaining on the market.